Review of Recent Research in the Bronze and Iron Age of the Northern Croatia - Potrebica, Hrvoje (2007)
The lecture presented recent research results related to the Bronze and Iron Age of the Northern Croatia to the members of the Hungarian Society of Archaeologists and Art Historians.
Projekt MZOS
ENG